Suspected hepatotoxicity and thrombocytopenia: Sodium valproate and carbamazepine - Siddhi Umarje; Arundhati Diwan; Asawari Raut (Wolters Kluwer Medknow Publications, 2018)
A young male was admitted in a tertiary care hospital with the complaints of excessive nausea, loose stools and fever with chills since few days. He was found to have thrombocytopenia, elevated liver enzymes, and suspected renal impairment. The patient was a known case of epilepsy, mood disorder and mental retardation. Since 6 months he was on sodium valproate, carbamazepine and trihexiphenidyl/risperidone fixed dose combination. Suspecting adverse drug reactions (thrombocytopenia, elevated liver enzymes), carbamazepine and sodium valproate were withdrawn. The patient was treated symptomatically with anti-pyretics and parentral fluids. On follow-up visit, the liver enzymes and platelet count were normal. The patient was maintained on levetiracetam and trihexiphenidyl/risperidone and the caretakers were counseled for the drugs therapy and monitoring parameters.